Reading, understanding, and applying nursing research - Fain, James A. , 1953- (F.A. Davis Company, 2021)
"This sixth edition of Reading, Understanding, and Applying Nursing Research has been updated while retaining all important features of previous editions. The book has been updated to better guide students in their understanding of evidence-based practice. The book continues to be directed toward undergraduate students, RNs returning to school, and practicing nurses. This edition continues to emphasize how to read research reports, evaluate them critically, and apply findings to practice by providing more examples of nursing research throughout the book. Steps of the research process are illustrated with excerpts from studies that have been published in nursing literature"-- Provided by publisher